El juego como estrategia pedagógica en niños y niñas de educación inicial - Del Pozo Gavilánez, Adriana Karina (2025)
The practice of play as a learning tool has made it possible to achieve the objectives set out in the curriculum, as well as the needs of integral development from an early age. In order to better understand the benefits obtained with its application in early childhood education, this article has posed the following research question: What is the role of play as a pedagogical strategy for children at the early childhood level? The main objective has been to understand the main postulates on the benefits of play in the classroom as part of the educational process, oriented towards the integral development of the child. The main findings were that play is a key pedagogical strategy in early education, since it promotes the integral growth of children through the exploration of their environment, the assimilation of experiences and the interaction with their peers. In this process, teachers play the role of facilitators between the play experience and the assimilation of formal concepts such as numbers and letters, in the socio-affective area, fostering the growth of identity and self-esteem by providing a safe and efficient environment for interaction and experimentation. Finally, it is concluded that the variety of games are part of the integral development of the child, encouraging their application in different environments, using an infinite number of resources and above all allowing them to be an active part of their experience.